A Murray Edelman Framing Analysis of Metro TV’s News Coverage of the US–Israel–Iran Conflict to Support Public Critical Media Literacy - Faisal Ibrahim; Nawiroh Vera (Jurnal IPTEK Bagi Masyarakat, 2026)
This study is motivated by the increasing intensity of media coverage on the United States (U.S.)–Israel–Iran conflict and the role of media in constructing reality through framing. It aims to analyze how Metro TV frames the conflict using Murray Edelman’s framing model. This research employs a qualitative approach within a constructivist paradigm, with the unit of analysis being a news text titled “The Betrayal of the U.S.–Israel in Violating the Ceasefire with Iran.” Data were collected through audio-visual observation and documentation, and analyzed using categorization and rubrication devices. The findings indicate that Metro TV constructs reality through a dichotomous schema of “us” versus “them.” Iran is represented as a defensive, legitimate, and diplomatically oriented actor, while the U.S. and Israel are framed as aggressive, inconsistent, and violators of international norms. At the rubrication level, the conflict is positioned within the domains of international politics and humanitarian crisis, implicitly marginalizing economic and structural geopolitical dimensions. These findings confirm that media coverage is not neutral, but reflects ideological tendencies that shape public perception. This study contributes to political communication and media studies by reinforcing the role of media as an agent of symbolic construction in global conflict discourse. The findings in this study also show the importance of media literacy in understanding international conflict reporting, because media can construct reality through diction choices, actor labeling, and the highlighting of certain issues that have the potential to influence how audiences interpret an event.